2018
DOI: 10.1093/rheumatology/key016
|View full text |Cite
|
Sign up to set email alerts
|

TNF inhibitor treatment is associated with a lower risk of hand osteoarthritis progression in rheumatoid arthritis patients after 10 years

Abstract: TNFi treatment was associated with a reduced risk on radiographic hand OA progression in DIP joints but not in PIP joints after 10 years. Although the effect sizes are small, these results provide evidence for influence of TNF-α in hand OA pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Therefore, it is imperative to identify an important indicator of the severity of the disease through examining the expression level of inflammatory cytokines. For instance, previous researches have shown that tumour necrosis factor (TNF‐α) and interleukin (IL)‐1β are the main components of inflammation in RA . However, the current treatment of RA remains expensive, especially the costs of biological agents, surgery and rehabilitation treatment , and hence exploration for the molecular mechanism of RA is still essential to minimize the clinical and socioeconomic impacts of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to identify an important indicator of the severity of the disease through examining the expression level of inflammatory cytokines. For instance, previous researches have shown that tumour necrosis factor (TNF‐α) and interleukin (IL)‐1β are the main components of inflammation in RA . However, the current treatment of RA remains expensive, especially the costs of biological agents, surgery and rehabilitation treatment , and hence exploration for the molecular mechanism of RA is still essential to minimize the clinical and socioeconomic impacts of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, tackling inflammatory mechanisms appears to be helpful here, not only suggested by the short-term treatment success of glucocorticoids, 5 but also by the interesting finding that tumour necrosis factor inhibitor treatment is associated with a lower risk of hand OA progression in patients with RA. 23 A previous study, the digital osteoarthritis in refractory hand OA-study (DORA), evaluating adalimumab in patients with refractory hand OA, failed to demonstrate any clinical 50% improvement after 6 weeks. There were also no statistically significant differences for any of the secondary outcomes (number of painful joints and of swollen joints, morning stiffness, patient global assessments, functional index for hand OA and consumption of analgesics).…”
Section: Osteoarthritis Osteoarthritis Osteoarthritismentioning
confidence: 97%
“…TNF inhibition has also been investigated using IgG monoclonal antibodies (infliximab or adalimumab) or circulating receptor fusion protein (etanercept). Treatment with anti-TNF-α blockers has demonstrated a decrease in disease progression but not in symptoms in patients with hand OA ( Verbruggen et al, 2012 ; Kloppenburg et al, 2018 ; Loef et al, 2018 ).…”
Section: Current and Future Pharmaceutical Therapy For Oamentioning
confidence: 99%